Traveling Spirit Masters: Moroccan Gnawa and Music in the Global Marketplace. Deborah Kapchan, Wesleyan University Press. Middletown, CT. 2007, 325 pages - Watkins, Lee (International Library of African Music, 2011)
pages: 252-254
Keywords: African Music